Glass
Patent Information
- Application Number
- JP2023131549
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-10
- Publication Date
- 2025-02-21
AI Technical Summary
【0015】 本発明によれば、酸に対する十分な中和能及び化学的耐久性を同時に実現し、かつ樹脂と組み合わせた際に透明性を示すガラスを提供することができる。
Smart Images

Figure 2025026152000001 
Figure 2025026152000002
Abstract
Description
[Technical field]
[0001] The present invention relates to glass. [Background technology]
[0002] In the treatment of dental caries or defects, dental composite materials (hereinafter sometimes referred to as composite materials) made of resins and inorganic fillers are widely used instead of conventional metal materials. Such composite materials have excellent mechanical strength and durability, and are useful for restoring the shape of the target site and as adhesives for bonding dental materials to teeth.
[0003] In dental restoration treatment using such composite materials, from the viewpoint of aesthetics, transparency as close as possible to that of natural tooth tissue is required. In order to achieve such transparency by combining a resin and an inorganic filler, it is essential that the refractive index of the resin and the refractive index of the inorganic filler are equivalent.
[0004] In addition, when the oral cavity becomes acidic due to eating, drinking, or the adhesion of plaque (food residue, peeled mucous membrane, etc.), demineralization occurs in which calcium ions and other substances are eluted from the tooth structure, causing dental caries. Normally, saliva has the ability to neutralize acids, so the oral cavity is kept neutral at about pH 7, but there is a limit to this neutralizing ability. Therefore, the above-mentioned inorganic filling materials are also required to exhibit neutralizing ability in an acidic environment.
[0005] For example, Patent Document 1 discloses a glass containing Si, Al, K, Zr, etc. and having a refractive index (nd) of 1.518 or more and 1.533 or less as a dental filling material whose refractive index matches that of a resin.
[0006] However, the dental glass described in the above Patent Document 1 does not have the function of suppressing demineralization and has poor acid neutralizing ability, and therefore has a high possibility of causing dental caries.
[0007] Meanwhile, Patent Document 2 discloses a composition using fluoroaluminosilicate glass consisting of Si, Al, B, Na, and Sr. It is expected that divalent to tetravalent ions released from the fluoroaluminosilicate glass will improve the acid resistance of teeth, and that acid neutralization in the oral cavity and release of fluoride ions will improve the acid resistance of teeth. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2010-189261 A [Patent Document 2] JP 2015-227309 A Summary of the Invention [Problem to be solved by the invention]
[0009] However, while the glass used in the composition described in Patent Document 2 can exhibit sufficient acid neutralizing ability, it has a problem with chemical durability.
[0010] The present invention has been developed in view of the above circumstances, and an object of the present invention is to provide a glass suitable for a dental composition which simultaneously realizes sufficient acid neutralization ability and chemical durability, and which exhibits transparency when combined with a resin. [Means for solving the problem]
[0011] As a result of extensive research into achieving the above-mentioned object, the inventors have found that by using predetermined amounts of Si, Al, B, O and F as the basic composition, optimizing the contents of Sr and Zn, and further restricting the content of one or more of Li, Na and K to 0.50% or less, it is possible to obtain a glass suitable for a dental composition which simultaneously achieves sufficient acid neutralization ability and chemical durability, and which exhibits transparency when combined with a resin.
[0012] That is, the glass of the present invention is Si: 5.00% or more and 15.00% or less, Al: 2.00% or more and less than 6.00% Sr: 10.00% or more and 30.00% or less, Zn: 2.00% or more and 25.00% or less, B: 2.00% or more and 10.00% or less, F: 17.00% or more and 30.00% or less, O: 16.00% or more and 40.00% or less, Total of Li, Na, and K: 0% or more and 0.50% or less, Such a glass simultaneously realizes sufficient acid neutralization ability and chemical durability, and exhibits transparency when combined with a resin.
[0013] In the glass of the present invention, the glass powder is added to an aqueous acetic acid solution of pH 3.6 at 37° C. to a concentration of 20% by mass to prepare a glass mixture, and after immersion for one hour, the pH of the glass mixture is preferably 4.4 or higher, and the weight loss rate of the glass powder due to the immersion for one hour is preferably 0.40% by mass or less.
[0014] The glass of the present invention preferably has a refractive index (nd) at the d line of 1.500 to 1.600. Effect of the Invention
[0015] According to the present invention, it is possible to provide a glass which simultaneously realizes sufficient acid neutralization ability and chemical durability, and which exhibits transparency when combined with a resin. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Hereinafter, the present invention will be described in detail with reference to embodiments.
[0017] (Glass) The glass of one embodiment of the present invention (hereinafter sometimes referred to as "the glass of the present embodiment") comprises, in mass %, Si: 5.00% or more and 15.00% or less, Al: 2.00% or more and less than 6.00% Sr: 10.00% or more and 30.00% or less, Zn: 2.00% or more and 25.00% or less, B: 2.00% or more and 10.00% or less, F: 17.00% or more and 30.00% or less, O: 16.00% or more and 40.00% or less, Total of Li, Na, and K: 0% or more and 0.50% or less, The composition is characterized in that it comprises:
[0018] The glass of the present embodiment may contain other components (described later) in addition to the above-mentioned components (Si, Al, Sr, Zn, B, F, O, Li, Na, K). However, from the viewpoint of more reliably exhibiting a desired ability to neutralize an acid, sufficient chemical durability, and transparency when combined with a resin, the glass of the present embodiment preferably has a composition consisting of only the above-mentioned components. Here, "consisting only of the above-mentioned components" includes cases where impurity components other than the above-mentioned components are inevitably mixed in, specifically, the proportion of impurity components is 0.20 mass % or less.
[0019] First, the reason why the glass composition is limited to the above range in this embodiment will be described. Note that "%" indications regarding components refer to mass % unless otherwise specified.
[0020] <si> Si is an essential component in the glass of this embodiment, and is the main component that forms the network structure that serves as the skeleton of the glass. In addition, Si is a component that can increase the devitrification resistance and strength of the glass. However, if the Si content in the glass exceeds 15.00%, the meltability decreases. On the other hand, if the Si content in the glass is below 5.00%, the devitrification resistance is not sufficiently obtained. Therefore, in the glass of this embodiment, the Si content is set to a range of 5.00% or more and 15.00% or less. From the same viewpoint, the Si content is preferably 6.00% or more, more preferably 7.00% or more, and preferably 14.00% or less, and more preferably 13.00% or less. Examples of raw materials corresponding to Si include SiO2, Al2Si2O5(OH)4, Zn2SiO4, etc., and these may be used alone or in combination of two or more.
[0021] <al> Al is an essential component in the glass of this embodiment, and is a component that can form a network structure of the glass, improve the devitrification resistance, and lower the refractive index by adding Al together with Sr and the like. However, it has been found that Al also lowers the neutralization ability against acid. If the content of Al in the glass exceeds 6.00%, the neutralization ability against acid and the chemical durability of the glass are lowered. On the other hand, if the content of Al in the glass is below 2.00%, the refractive index of the glass increases. Therefore, in the glass of this embodiment, the content of Al is set to be in the range of 2.00% or more and less than 6.00%. From the same viewpoint, the content of Al is preferably 2.50% or more, more preferably 3.00% or more, and preferably 5.50% or less, and more preferably 5.00% or less. Examples of raw materials corresponding to Al include Al2O3, Al2Si2O5(OH)4, AlF3, etc., and these may be used alone or in combination of two or more.
[0022] <sr> Sr is an essential component in the glass of this embodiment, and is a component that can enhance the neutralizing ability against acid. Sr is also a component that can enhance X-ray contrast. However, if the Sr content in the glass exceeds 30.00%, the devitrification resistance decreases. On the other hand, if the Sr content in the glass is below 10.00%, the neutralizing ability against acid is not sufficiently obtained. Therefore, in the glass of this embodiment, the Sr content is set to a range of 10.00% or more and 30.00% or less. From the same viewpoint, the Sr content is preferably 11.00% or more, more preferably 12.00% or more, and preferably 29.00% or less, and more preferably 28.00% or less. Examples of raw materials corresponding to Sr include SrCO3, SrF2, etc., and these may be used alone or in combination of two or more.
[0023] <zn> Zn is an essential component in the glass of this embodiment, and is a component that can improve the chemical durability of the glass. Zn is also a component that can improve X-ray contrast. However, if the Zn content in the glass exceeds 25.00%, the refractive index of the glass increases. On the other hand, if the Zn content in the glass is below 2.00%, the chemical durability of the glass is not sufficiently obtained. Therefore, in the glass of this embodiment, the Zn content is set to a range of 2.00% or more and 25.00% or less. From the same viewpoint, the Zn content is preferably 3.00% or more, more preferably 4.00% or more, and preferably 24.00% or less, and more preferably 23.00% or less. Examples of raw materials corresponding to Zn include ZnO, ZnF2, etc., and these may be used alone or in combination of two or more.
[0024] B is an essential component in the glass of this embodiment, and is the main component that forms a network structure that serves as the skeleton of the glass. In addition, B is a component that can increase the devitrification resistance and meltability of the glass. However, if the content of B in the glass exceeds 10.00%, the chemical durability of the glass decreases. On the other hand, if the content of B in the glass is below 2.00%, the devitrification resistance is not sufficiently obtained. Therefore, in the glass of this embodiment, the content of B is set to a range of 2.00% or more and 10.00% or less. From the same viewpoint, the content of B is preferably 3.00% or more, more preferably 4.00% or more, and preferably 9.00% or less, and more preferably 8.00% or less. Examples of raw materials corresponding to B include B2O3, H3BO3, etc., and these may be used alone or in combination of two or more.
[0025] <f> F is an essential component in the glass of this embodiment, and is a component that can improve the chemical durability of the glass. In addition, it is expected that the acid resistance of the tooth substance will be improved by releasing fluoride ions. However, if the content of F in the glass exceeds 30.00%, the devitrification resistance will decrease. On the other hand, if the content of F in the glass is below 17.00%, the chemical durability of the glass will not be sufficient. Therefore, in the glass of this embodiment, the content of F is set to a range of 17.00% or more and 30.00% or less. From the same viewpoint, the content of F is preferably 18.00% or more, more preferably 19.00% or more, and preferably 29.00% or less, and more preferably 28.00% or less. Examples of raw materials corresponding to F include AlF3, SrF2, ZnF2, and NH4F, and these may be used alone or in combination of two or more.
[0026] <o> O is an essential component in the glass of this embodiment, and is the main component that forms the network structure that serves as the skeleton of the glass. O is also a component that can improve devitrification resistance. However, if the content of O in the glass exceeds 40.00%, the neutralization ability against acid is insufficient. On the other hand, if the content of O in the glass is below 16.00%, the devitrification resistance decreases. Therefore, in the glass of this embodiment, the content of O is set to a range of 16.00% or more and 40.00% or less. From the same viewpoint, the content of O is preferably 17.00% or more, more preferably 18.00% or more, even more preferably 20.00% or more, even more preferably 22.00% or more, and preferably 39.00% or less, more preferably 38.00% or less, even more preferably 35.00% or less, and even more preferably 32.00% or less. Examples of raw materials corresponding to O include various oxides such as SiO2, B2O3, and Al2O3, and these may be used alone or in combination of two or more.
[0027] <Li、Na、K> Li, Na, and K are optional components in the glass of this embodiment. These components improve the meltability of the glass. However, if the total content of Li, Na, and K in the glass exceeds 0.50%, sufficient devitrification resistance cannot be obtained. Therefore, in the glass of this embodiment, the total content of Li, Na, and K is set to a range of 0.50% or less. From the same viewpoint, the total content of Li, Na, and K is preferably 0.40% or less, more preferably 0.30% or less. In addition, the content of each of the Li, Na, and K components is preferably 0.35% or less, more preferably 0.30% or less. Examples of raw materials corresponding to Li include Li2CO3 and LiF. Examples of raw materials corresponding to Na include Na2CO3, NaF, and Na3AlF6. Examples of raw materials corresponding to K include K2CO3, KF, and K2SiF6. These may be used alone or in combination of two or more.
[0028] <Other ingredients> The glass of the present embodiment may contain small amounts (for example, such that the total amount of these is 3 mass % or less) of other components than those described above, such as Mg, Ca, Ba, P, Sc, Ti, Y, Zr, Ta, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, etc., so long as the purpose is not exceeded. Note that it is preferable that the glass of the present embodiment does not contain components that have a high load on the environment and a high adverse effect on the human body, such as Cr, Co, Ni, Pb, Te, As, and Cd.
[0029] Next, various characteristics of the glass of this embodiment will be described.
[0030] <Refractive index (nd)> In order to ensure transparency, the glass of this embodiment preferably has a refractive index that is approximately equal to that of the resin formed by adding a polymerization initiator to a polymerizable monomer and hardening the resin. Hydroxyapatite, which is a main component of natural teeth, has a refractive index of about 1.6, but the above-mentioned natural teeth, which have a composite structure, have a slightly lower apparent refractive index. For this reason, it is said that a dental composite material with a refractive index adjusted to about 1.500 to 1.600 can be used to achieve a natural appearance. The refractive index of the resin is determined by the polymerizable monomer, and for example, the refractive index (nd) at the d line can be 1.500 or more and 1.600 or less by mixing and hardening BMHPE, UDMA, POBMA, etc. in a predetermined ratio. Therefore, the glass of this embodiment preferably has a refractive index (nd) at the d line of 1.500 or more and 1.600 or less to be equal to that of the resin. The refractive index (nd) can be measured by the procedure described in the Examples. The refractive index (nd) of the glass of the present embodiment can be adjusted, for example, by appropriately adjusting the content of each of the above-mentioned components within a predetermined range.
[0031] <pH after immersion in acidic solution> The glass of the present embodiment preferably has a property of increasing the pH by a neutralization reaction in an acidic environment in order to prevent dental caries. More specifically, the glass of the present embodiment is prepared by adding the glass powder to an aqueous acetic acid solution of pH 3.6 at 37° C. so as to have a concentration of 20 mass % to prepare a glass mixture, and after immersion for 1 hour, the glass mixture preferably has a pH of 4.4 or more. The pH after immersion in the acidic solution can be measured by the procedure described in the Examples. The pH after immersion in the acidic solution can be adjusted, for example, by appropriately adjusting the content of each of the above-mentioned components within a predetermined range.
[0032] <Weight loss rate of glass sample after immersion in acidic solution> The glass of this embodiment preferably has a small weight loss rate of a glass sample in an acidic environment as an index of good chemical durability. More specifically, the glass of this embodiment is preferably a glass mixture obtained by adding the glass powder to an aqueous acetic acid solution of pH 3.6 at 37° C. to a concentration of 20 mass % to prepare a glass mixture, and after immersing the glass powder for 1 hour, the weight loss rate of the glass powder is preferably 0.40 mass % or less. The weight loss rate of the glass sample after immersion in the acidic liquid can be measured by the procedure described in the Examples. The weight loss rate of the glass sample after immersion in the acidic liquid can be adjusted, for example, by appropriately adjusting the content of each of the above-mentioned components within a predetermined range.
[0033] <Glass manufacturing method> Next, a method for producing the glass of the present embodiment will be described. Here, the glass of the present embodiment may be produced by any method as long as the composition of each component satisfies the above-mentioned range, and the method for producing the glass is not particularly limited, and the glass can be produced by any conventional method. For example, first, oxides, fluorides, hydroxides, carbonates, nitrates, etc. are weighed in a predetermined ratio as raw materials of each component that can be contained in the glass of this embodiment, and mixed thoroughly to prepare a glass compound raw material. Next, this raw material is charged into a melting vessel (e.g., a crucible made of a precious metal such as platinum) that is not reactive with the glass raw materials, and heated to 1000 to 1400°C in an electric furnace to melt. After that, the mixture is stirred appropriately to homogenize, clarified, and then rapidly cooled to produce glass.
[0034] <Application> The glass of the present embodiment simultaneously realizes sufficient neutralization ability against acid and chemical durability as described above, and exhibits transparency when combined with a resin, and therefore can be used, for example, in a dental composition (dental composite material). In other words, the glass of the present embodiment may be, for example, a dental glass. Such a dental composition contains, for example, at least the glass of the present embodiment as an inorganic filler material, and a resin formed by hardening by adding a polymerization initiator to a polymerizable monomer.
[0035] As the polymerizable monomer for forming the resin in the dental composition, any polymerizable monomer known to be used in dental compositions can be used. For example, 1,2-bis(3-methacryloyloxy-2-hydroxypropoxy)ethane (BMHPE), 2,2,4-trimethylhexamethylenebis(2-carbamoyloxyethyl)dimethacrylate (UDMA), m-phenoxybenzyl methacrylate (POBMA), etc. can be mentioned. These polymerizable monomers may be used alone or in combination of two or more kinds.
[0036] As the polymerization initiator for forming the resin in the dental composition, a polymerization initiator known to be used in dental compositions can be used. For example, camphorquinone (CQ), 4-N,N-dimethylamino ethyl benzoate (PDE), etc. can be mentioned. These polymerization initiators may be used alone or in combination of two or more.
[0037] The dental composition may be produced by any method as long as it uses the glass of the present embodiment, and the method for producing the dental composition is not particularly limited, and the dental composition may be produced by any conventional method. For example, first, the glass of the present embodiment described above is pulverized with a ball mill. Next, 100 parts by mass of the obtained pulverized glass is surface-treated with 1.5 parts by mass of γ-methacryloyloxypropyltrimethoxysilane by a conventional method to obtain a silane-treated glass powder. Next, the silane-treated glass powder, the polymerizable monomers BMHPE and UDMA, and the polymerization initiators CQ and PDE are weighed in a predetermined ratio, and thoroughly mixed and kneaded at room temperature to obtain a dental mixture paste. Next, the dental mixture paste is irradiated with light using a dental LED light irradiator to harden the paste, thereby producing a dental composition containing the glass of the present embodiment and a resin. EXAMPLES
[0038] EXAMPLES The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to these examples.
[0039] As the raw materials for each component, at least one of the corresponding oxides, fluorides, carbonates, and nitrates was prepared, weighed so that the composition after vitrification would be as shown in Tables 1 and 2, and thoroughly mixed to obtain a blended raw material. This blended raw material was placed in a platinum crucible and melted in an electric furnace. The temperature during melting was appropriately adjusted within the range of 1000 to 1400°C in order to achieve sufficient defoaming. After that, the mixture was stirred at an appropriate time to homogenize, clarified, and then rapidly cooled to obtain glass (there were also cases where glass was not obtained). In addition, the blended raw materials were melted and homogenized in the same procedure, cast into a mold preheated to an appropriate temperature, and then slowly cooled in an electric furnace to remove distortion, to obtain glass for refractive index measurement.
[0040] Next, for each of the glasses obtained, the refractive index (nd), pH after immersion in an acidic solution, and the weight loss rate of the glass sample due to immersion in an acidic solution were measured according to the procedures described below. Note that these measurements were not performed for examples in which the above-mentioned glasses were not obtained. The results are shown in Tables 1 and 2.
[0041] <Refractive index> The refractive index (nd) at d line was measured using the above-mentioned glass for refractive index measurement in accordance with the refractive index measurement method of JIS B 7071-2. If the refractive index (nd) at d line is 1.500 or more and 1.600 or less, the glass is advantageous in terms of transparency when combined with a resin.
[0042] <pH after immersion in acidic solution> The glass obtained by quenching was crushed in a mortar, passed through a 30 mesh sieve, and obtained glass powder of a size that remained on a 40 mesh sieve. 1.0000g of glass powder was put into a test tube, and then 4.0ml of an acetic acid solution with a pH of 3.6 was put into the test tube to prepare a glass mixture (i.e., a glass concentration of 20% by mass), and the mixture was immersed in a thermostatic water bath set at 37°C for 1 hour. After that, the test tube was taken out, and 0.5ml of the supernatant of the glass mixture was taken, and the pH was measured with a compact pH meter (LAQUAtwin, manufactured by HORIBA Seisakusho). If the measured pH is 4.4 or higher, it indicates that the glass has good neutralizing ability against acids. The pH meter was calibrated using standard solutions of pH 4.01 and pH 6.86 before use.
[0043] <Weight loss rate of glass sample after immersion in acidic solution> Before immersion in the acid solution, the mass of the test tube itself (M TC The mass of the test tube after adding the glass powder (M TC+bS ) to find the mass of the test tube itself (M TC ) to obtain the mass of the glass powder (glass sample) before immersion in the acid solution (M bS =M TC+bS -M TC ) was calculated. Next, after the addition of the aqueous acetic acid solution and the immersion, 5 ml of ethanol was added to the test tube after the pH measurement, and the supernatant was removed by decantation. After the decantation method was repeated three times, the tube was dried at 100°C for one hour in a dryer. The mass (M TC+aS ) to find the mass of the test tube itself (M TC ) to obtain the mass of the glass sample after immersion in the acid solution (M aS =M TC+aS -M TC The weight loss rate of the glass sample after immersion in the acidic solution was calculated as (M bS -M aS ) / M bS × 100. A smaller calculated value, particularly 0.40% or less, indicates better chemical durability.
[0044] [Table 1]
[0045] [Table 2]
[0046] From Table 1, it can be seen that the glasses of Examples 1 to 10 all had a pH of 4.4 or more after immersion in an aqueous acetic acid solution, and thus had good acid neutralization ability. In addition, the glass samples of Examples 1 to 10 all had a weight loss of 0.40% or less after immersion in an aqueous acetic acid solution, and thus had sufficient chemical durability. Furthermore, the glasses of Examples 1 to 10 all had a refractive index of 1.500 or more and 1.600 or less, and thus were advantageous in terms of transparency when combined with a resin.
[0047] In contrast to this, from Table 2, in Comparative Example 1, the weight loss rate of the glass sample after immersion in the acidic liquid was small, but the pH after immersion in the acidic liquid was less than pH 4.4. In Comparative Example 2, the pH after immersion in the acidic liquid was 4.4 or more, but the weight loss rate of the glass sample after immersion in the acidic liquid exceeded 0.40%.
[0048] Moreover, in Comparative Example 3, devitrification occurred and glass could not be obtained, which is believed to be due to an excessively small amount of Si, etc. In Comparative Example 4, the melting property was poor even at 1400° C., so that devitrification occurred and glass could not be obtained. This is considered to be due to an excessive amount of Si, etc.
[0049] In addition, in Comparative Example 5, the refractive index exceeded 1.600. This is considered to be due to the fact that the amount of Al was too small, etc. In Comparative Example 6, the pH was less than 4.4. Furthermore, the weight loss rate of the glass sample after immersion in the acidic liquid exceeded 0.40%, which is believed to be due to an excessive amount of Al.
[0050] In Comparative Example 7, the pH was less than 4.4, which is believed to be due to an excessively small amount of Sr. In Comparative Example 8, devitrification occurred and glass could not be obtained, which is believed to be due to an excessive amount of Sr, etc.
[0051] In Comparative Example 9, the weight loss rate of the glass sample after immersion in the acidic solution exceeded 0.40%, which is believed to be due to an excessively small amount of Zn, etc. In Comparative Example 10, devitrification occurred and glass could not be obtained, which is believed to be due to an excessive amount of Zn, etc.
[0052] In Comparative Example 11, devitrification occurred and glass could not be obtained. This is believed to be due to an excessively small amount of B, etc. In Comparative Example 12, the weight loss rate of the glass sample after immersion in the acidic liquid exceeded 0.40%, which is believed to be due to an excessive amount of B, etc.
[0053] In Comparative Example 13, the weight loss rate of the glass sample after immersion in the acidic liquid exceeded 0.40%, which is believed to be due to an excessively small amount of F, etc. In Comparative Example 14, devitrification occurred and glass could not be obtained. This is believed to be due to the fact that the amounts of F and O were too small.
[0054] In Comparative Example 15, devitrification occurred and glass could not be obtained. This is believed to be due to the fact that any one or more of Li, Na and K was contained in an excessive amount. [Industrial Applicability]
[0055] According to the present invention, it is possible to provide a glass which simultaneously realizes sufficient acid neutralization ability and chemical durability, and which exhibits transparency when combined with a resin.< / o> < / f> < / zn> < / sr> < / al> < / si>
Claims
1. In mass percent, Si: 5.00% or more and 15.00% or less, Al: 2.00% or more and less than 6.00%; Sr: 10.00% or more and 30.00% or less, Zn: 2.00% or more and 25.00% or less, B: 2.00% or more and 10.00% or less, F: 17.00% or more and 30.00% or less, O: 16.00% or more and 40.00% or less, Total of Li, Na, and K: 0% or more and 0.50% or less, A glass having a composition comprising:
2. 2. The glass according to claim 1, wherein the glass powder is added to an aqueous acetic acid solution having a pH of 3.6 at 37° C. so as to have a concentration of 20% by mass to prepare a glass mixed solution, and the glass mixed solution is immersed for one hour, after which the pH of the glass mixed solution is 4.4 or higher, and a weight loss rate of the glass powder due to the immersion for one hour is 0.40% by mass or less.
3. 3. The glass according to claim 1, having a refractive index (nd) at d line of 1.500 to 1.600.
Citation Information
Patent Citations
Barium-free radiopaque glass and the use thereof
JP2010189261A
Neutralization-facilitating ion sustained-release dental film
JP2015227309A